Are the TTAGG and TTAGGG telomeric repeats phylogenetically conserved in aculeate Hymenoptera? - Menezes, Rodolpho S T; Bardella, Vanessa B.; Cabral-de-Mello, Diogo C.; Lucena, Daercio A A; Almeida, Eduardo A B (Springer Nature, 2017)
Despite the (TTAGG)n telomeric repeat supposed being the ancestral DNA motif of telomeres in insects, it was repeatedly lost within some insect orders. Notably, parasitoid hymenopterans and the social wasp Metapolybia decorata (Gribodo) lack the (TTAGG)n sequence, but in other representatives of Hymenoptera, this motif was noticed, such as different ant species and the honeybee. These findings raise the question of whether the insect telomeric repeat is or not phylogenetically predominant in Hymenoptera. Thus, we evaluated the occurrence of both the (TTAGG)n sequence and the vertebrate telomere sequence (TTAGGG)n using dot-blotting hybridization in 25 aculeate species of Hymenoptera. Our results revealed the absence of (TTAGG)n sequence in all tested species, elevating the number of hymenopteran families lacking this telomeric sequence to 13 out of the 15 tested families so far. The (TTAGGG)n was not observed in any tested species. Based on our data and compiled information, we suggest that the (TTAGG)n sequence was putatively lost in the ancestor of Apocrita with at least two subsequent independent regains (in Formicidae and Apidae).
Keywords: Apocrita; Chromosomes; Evolution; Insects; Telomere; TTAGG